Control of magnetic anisotropy by orbital hybridization with charge transfer in (La0.67Sr0.33MnO3)n/(SrTiO3)n superlattice. (September 2018) - Zhang, Bangmin; Wu, Lijun; Zheng, Jincheng; Yang, Ping; Yu, Xiaojiang; Ding, Jun; Heald, Steve; Rosenberg, Richard; Venkatesan, Thirumalai; Chen, Jingsheng; Sun, Cheng-Jun; Zhu, Yimei; et al.
Abstract The chemical asymmetry at the hetero-structure interface offers an effective opportunity to design desirable electronic structures by controlling charge transfer and orbital hybridization across the interface. However, controlling the hetero-interface remains a daunting task. Here, we report the modulation of interfacial coupling of (La0.67 Sr0.33 MnO3 )n /(SrTiO3 )n superlattices by manipulating the periodic thickness withn unit cells of SrTiO3 andn unit cells of La0.67 Sr0.33 MnO3 with a fixed thickness of 120 unit cells. The easy axis of magnetic anisotropy rotates 45° towards the out-of-plane direction fromn = 10 ton = 2 at reduced temperatureT Re = T /T S = 0.87, whereT S is the temperature at the onset of magnetization. Transmission electron microscopy reveals an enlarged tetragonal ratio >1 with breaking of volume conservation around the (La0.67 Sr0.33 MnO3 )n /(SrTiO3 )n interface and electronic charge transfer from Mn to Ti 3d orbitals across the interface. Orbital hybridization accompanying the charge transfer results in preferred occupancy of 3d_3z^2-r^2 3 d 3 z 2 - r 2 orbitals at the interface and induces a stronger electronic hopping integral and interfacial magnetic anisotropy along the out-of-plane direction, which contributes to the rotation towards the out-of-plane direction of an effective magnetic easy axis forn = 2. We demonstrate that interfacial orbital hybridization with charge transfer in the superlattice of strongly correlated oxides may be a promising approach to tailor electronic and magnetic properties in device applications. Magnetic materials: Stacking layers for an easy rotation A composite material with tuneable magnetic properties which could add novel functionality to electronic devices has been developed by scientists from Singapore and the USA. The interface between two crystalline materials can exhibit properties differing from those of either substance separately. These interface properties can be extended to three dimensions by stacking alternating thin layers of the two materials, creating a so-called superlattice. Bangmin Zhang from the National University of Singapore and co-workers used this concept to alter the magnetic response of a superlattice consisting of lanthanum strontium manganite and strontium titanate. They showed that they could rotate the direction along which the smallest magnetic field is required to magnetize the material by changing the thickness of the layers. This could be useful in devices that are controlled by interaction between electric and magnetic fields. The modulation of interfacial coupling of (La0.67 Sr0.33 MnO3 )n /(SrTiO3 )n superlattices withn unit cells of SrTiO3 andn unit cells La0.67 Sr0.33 MnO3, offers an effective opportunity to control charge transfer and orbital hybridization. The easy axis of magnetic anisotropy rotates 45° towards the out-of-plane direction fromn = 10 ton = 2 at reduced temperatureT Re = T /T S = 0.87 (T S is onset of magnetization). Orbital hybridization accompanying the charge transfer results in preferred occupancy of 3d_3z_2 - r_2 3 d 3 z 2 - r 2 orbital at the interface, and induces stronger electronic hopping integral and interfacial magnetic anisotropy along perpendicular direction, useful to tailor properties in device applications.